Association of cerebral white matter disease with cardiovascular risk factors, amyloid accumulation, and cognition: Amyloid imaging. (7th December 2020) - Cody, Karly Alex; Berman, Sara E; Koscik, Rebecca L.; Rivera‐Rivera, Leonardo A; Hoffman, Carson A; Erickson, Claire M; Mueller, Kimberly D; Clark, Lindsay R; Chin, Nathaniel A.; Christian, Bradley T; Rowley, Howard A.; Wieben, Oliver; et al.
Abstract: Background: Understanding cerebrovascular health in Alzheimer's disease (AD) is vital, as the majority of individuals with dementia due to AD are also found to have vascular disease at autopsy. We examined the relationships between centrally and peripherally measured vascular health markers and amyloid accumulation across the AD clinical spectrum. Method: Cerebral white matter (WM) disease was determined by a neuroradiologist using the Cardiovascular Health Study (CHS) score in 236 individuals (75% cognitively healthy, 25% cognitively impaired; Table 1) from the Wisconsin ADRC and WRAP cohorts. A subset (n = 73) of individuals completed [C‐11]PiB PET imaging. Metrics of internal carotid arterial (ICA) health assessed by 4D‐flow MRI as well as WM hyperintensity lesion volume (WMH‐LV), amyloid accumulation, vascular risk factors, and cognitive status were examined across individuals with high (≥3) and low (<3) CHS scores (Table 2, Figures 1 & 2). A threshold for vascular positivity (V+/‐) was identified as 1.5SD>the mean %WMH‐LV of total intracranial volume in individuals with CHS<3. Participants were classified according to their amyloid and vascular positivity status. Result: In the larger dataset (n = 236), individuals with CHS≥3 were significantly older, more likely to be cognitively impaired, and demonstrated higher pulse pressure, lower cholesterol, and greater %WMH‐LV (Table 1, Figure 1). There was no difference between CHS groups in average ICA blood flow, ICA pulse wave velocity, or global PiB accumulation (Table 2). Neither CHS rating nor %WMH‐LV were associated with amyloid (Spearman's rho = ‐.128, p = .280; Spearman's rho = .078, p = .511, respectively). When using %WMH‐LV as a biomarker for cerebrovascular health, the vascular positivity threshold was 0.409%. In individuals with amyloid imaging, 54.8%(38/73) were V‐/A‐, 8.2%(8/73) were V+/A‐, 34.2%(24/73) were V‐/A+, and (2/73)0.8% were V+/A+. CHS rating and vascular positivity were not related to cognitive diagnosis in the amyloid imaging subset (Figure 2). Conclusion: Elevated cerebral WM disease (CHS≥3) was related to greater WMH lesion burden, but not blood flow or pulse wave velocity of the ICAs. Thus far, in this sample spanning the continuum of AD, neuroimaging measures of vascular health were not related to amyloid, suggesting independence of these pathologies. Investigations into the associations between amyloid, cerebrovascular health, and cognition are ongoing as more data become available.